Long-term gonadal hormone treatment and endogenous neurogenesis in the dentate gyrus of the adult female monkey - Kordower, Jeffrey H. (2010)
Neurogenesis occurs continually throughout life in all mammals and the extent of neurogenesis is influenced by many factors including gonadal hormones. Most research regarding hormones and neurogenesis has been performed on non-primate species. To determine whether gonadal hormones can modulate endogenous neurogenesis in the dentate gyrus (DG) of the hippocampus in non-human primates, ovariectomized (OVX) female rhesus monkeys received continuous, unopposed β-estradiol (OVX-E-Con), cyclic unopposed β-estradiol (OVX-E-Cyc), continuous β-estradiol + cyclic progesterone (OVX-E-Con+P-Cyc), or control (OVX-Veh) treatments. At week 29, all monkeys received BrdU injections for four consecutive days, in addition to the ongoing treatment. Twenty days after the last BrdU injection, all animals were sacrificed for tissue collection. In DG of hippocampus, scattered BrdU-ir cells were observed mainly in the subgranular zone (SGZ) and in the granule cell layer and occasionally these BrdU-ir cells in the SGZ formed clusters containing between 2–5 cells. In the granule cell layer and SGZ, virtually none of the BrdU-ir cells were either Dcx, a marker of immature neurons, or GFAP positive. However, an occasional BrdU-ir cell was positive for both neuronal marker NeuN or β III-tubulin. Unbiased stereological analysis of BrdU-ir cells within the SGZ and the granule cell layer of DG revealed that among the experimental groups, there was no significant difference in number of BrdU-ir cells within the SGZ and the granule cell layer of the DG: OVX-E-Con (1801+218.7), OVX-E-Cyc (1783+415.6), OVX-E-Con+P-Cyc (1721+229.6), and OVX-Veh (1263+106.3), but a trend towards increased BrdU-ir cells was observed in all the experimental groups.